ROLE OF SOMVALK KASHAY ASTHAPAN BASTI IN PRAMEHA W.S.R TO (DIABETES MELLITUS TYPE 2) (AYUSHDHARA, 2019)
The disease diabetes currently affects more than 62 million people which is more than 7.1% of India’s adult population. The prevalence rate of diabetes in urban and rural areas is 10.3% and 6.2% respectively.The Aim of the study is standardization of the method of preparation and administration of Somvalk Kashay Asthapan Basti and Somvalk Siddha Taila Anuvasan Basti. Two groups Group A (Trial Group) 50 patients is given Somvalkkashayasthapan Basti, and Somvalk siddhataila anuvasanbasti along with Metformin for 12 days and Group B (Control Group) 50 patients is given oral hypoglycemic drug and Metformin will be given according to the dosage 12 days.Group A showed moderate improvement, while Group B showed no improvement. The overall result obtained in the present study  shows 65% improvement in trial group which is moderate improvement according to the overall assessment criteria, whereas there was only 18% improvement in the control group which falls within unimproved category according to the overall assessment criteria.The trial drug in the study i.e., Somvalk kasha Asthapanbasti has been proved significantly effective in symptoms like Polyuria, polydipsia, polyphagia and urine sugar. It has shown moderate effects on the symptoms like numbness and tingling. It has shown mild improvement in parameters of BSL- Fasting and BSL- PP.